Nas horas da tradução: uma leitura do romance As horas, de Michael Cunningham - Silva, Eder Menezes da (2008)
We aim to realize an analises of the book The hours written by a north- american author Michael Cunningham by the translation perspective, understood in this context, while practice of the difference between the england culture and the north-american culture, considerring that Cunningham realizes a new critical lecture from the english romance called Mrs. Dalloway, written by Virginia Woolf. In this way, intend its to propose reflexions concerning of the construction process of the romance by means of we understand for cultural translation and this term will be discuted appropriatally in this work’s structure. It's relevant to stand out some modalities which will be noted in the chapters and they will be followed in this order: the literary appropriation, the cultural translation, the negociation, the lecture, the pastiche and the filmic adaptation.